Growth phase‐dependent surface properties of Legionella pneumophila and their role in adhesion to stainless steel coated QCM‐D sensors. (3rd June 2021) - Ariyadasa, S.; Abeysekera, G.; Billington, C.; Fee, C.; Pang, L.
Abstract: Legionella pneumophila cell surface hydrophobicity and charge are important determinants of their mobility and persistence in engineered water systems (EWS). These surface properties may differ depending on the growth phase of L. pneumophila resulting in variable adhesion and persistence within EWS. We describe the growth‐dependent variations in L. pneumophila cell surface hydrophobicity and surface charge using the microbial adhesion to hydrocarbon assay and microelectrophoresis, respectively, and their role in cell adhesion to stainless steel using a quartz crystal microbalance with dissipation (QCM‐D) monitoring instrument. We observed a steady increase in L. pneumophila hydrophobicity during their lifecycle in culture media. Cell surfaces of stationary phase L. pneumophila were significantly more hydrophobic than their lag and midexponential counterparts. No significant changes in L. pneumophila cell surface charge were noted. Morphology of L. pneumophila remained relatively constant throughout their lifecycle. In the QCM‐D study, lag and exponential phase L. pneumophila weakly adhered to stainless steel surfaces resulting in viscoelastic layers. In contrast, stationary phase bacteria were tightly and irreversibly bound to the surfaces, forming rigid layers. Our results suggest that the stationary phase of L. pneumophila would highly favour their adhesion to plumbing surfaces and persistence in EWS. Abstract : Significance and Impact of the Study: The role of growth phase‐dependent variations in cell surface hydrophobicity and charge on adhesion of the opportunistic pathogen Legionella pneumophila to plumbing materials remains poorly described. In this study, we characterized the effect of L. pneumophila cell surface properties on adhesion to stainless steel, an increasingly used plumbing material in potable water systems. These results help us understand the persistence of L. pneumophila in engineered water systems. To our knowledge, this is the first report describing the role of growth‐dependent variations of L. pneumophila cell surface properties in adhesion to a plumbing material surface.